The impact economy: Balancing profit and impact - Dirk Schoenmaker (Bruegel, 2020)
How can governments and companies be jointly empowered to have a positive impact on the sustainable development goals? The current economic system is largely geared towards increasing economic growth. But this could come at the expense of rising social inequality and environmental degradation.This paper examines the link between economic system outcomes and corporate sustainability outcomes. We provide evidence that governments and companies can reinforce each other in their pursuit of sustainable development. Sustainable development is based on three pillars: economic, social and environmental. These pillars should be assessed and balanced in an integrated way. An impact economy, in which governments and companies balance profit and impact, is best placed to achieve the sustainable development goals.
Keywords: 330; Sustainable development goals; corporate governance; economic governance; social impacts; environmental impacts